163k views
3 votes
(Factorise) 3m(Square) - 16mn - 12n (Square)

User JakeHova
by
5.8k points

1 Answer

3 votes

Answer:

(m - 6n)(3m + 2n)

Explanation:

Given

3m² - 16mn - 12n²

Consider the factors of the product of the coefficient of the m² term and the n² term which sum to give the coefficient of the mn term

product = 3 × - 12 = - 36 and sum = - 16

The factors are - 18 and + 2

Use these factors to split the mn term

3m² - 18mn + 2mn - 12n² ( factor the first/second and third/fourth terms )

= 3m(m - 6n) + 2n(m - 6n) ← factor out (m - 6n) from each term

= (m - 6n)(3m + 2n)

User Mpyw
by
5.3k points